Analisis Hukum Persaingan Usaha Platform Marketplace Online Pada Era Ekonomi Digital - Kennedy, Alexander (Ethics and Law Journal: Business and Notary, 2024)
The development of the digital economy in Indonesia has led to the emergence of online marketplace platforms that implement policies requiring sellers to offer products at prices equal to or lower than on other platforms. This study analyzes the legal implications of such policies on business competition and their impact on sellers and consumers within the online marketplace ecosystem. The research method used is normative juridical, analyzing applicable laws and regulations, particularly Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Secondary data from legal literature, academic journals, and relevant case studies are used to evaluate the compliance of platform policies with the principles of competition law. This study results show that platform policies limiting sellers’ pricing autonomy potentially violate Article 5, Article 17, and Article 25 of Law No. 5 of 1999, which prohibit price-fixing and abuse of dominant position. These policies restrict sellers' autonomy, reduce profit margins, and may inhibit healthy competition between platforms. The negative impact on small and medium sellers can also harm consumers in the long term by reducing product choices and innovation. This study recommends reevaluating platform policies, strengthening the role of the Business Competition Supervisory Commission (KPPU) in oversight, developing specific regulations for the digital economy, educating sellers and consumers, and implementing ethical business practices by platforms. Through these measures, a healthy, fair, and sustainable digital economic ecosystem in Indonesia can be achieved. Abstrak Perkembangan ekonomi digital di Indonesia telah memunculkan platform pasar daring yang menerapkan kebijakan meminta penjual menjual produk dengan harga lebih rendah atau sama dengan platform lain. Penelitian ini menganalisis implikasi hukum dari kebijakan tersebut terhadap persaingan usaha serta dampaknya bagi penjual dan konsumen dalam ekosistem pasar daring. Metode penelitian yang digunakan adalah yuridis normatif, dengan menganalisis peraturan perundang-undangan yang berlaku, khususnya Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktik Monopoli dan Persaingan Usaha Tidak Sehat. Data sekunder dari literatur hukum, jurnal ilmiah, dan studi kasus terkait digunakan untuk mengevaluasi kesesuaian kebijakan platform dengan prinsip-prinsip hukum persaingan usaha. Hasil penelitian menunjukkan bahwa kebijakan platform yang membatasi penetapan harga oleh penjual berpotensi melanggar Pasal 5, Pasal 17, dan Pasal 25 UU No. 5 Tahun 1999, yang melarang pengaturan harga dan penyalahgunaan posisi dominan. Kebijakan ini membatasi otonomi penjual, menekan margin keuntungan, dan dapat menghambat persaingan sehat antar platform. Dampak negatif terhadap penjual kecil dan menengah juga dapat merugikan konsumen dalam jangka panjang melalui berkurangnya pilihan produk dan inovasi. Penelitian ini merekomendasikan evaluasi ulang kebijakan oleh platform pasar daring, peningkatan peran Komisi Pengawas Persaingan Usaha (KPPU) dalam pengawasan, pengembangan regulasi khusus untuk ekonomi digital, edukasi bagi penjual dan konsumen, serta penerapan etika bisnis oleh platform. Dengan langkah-langkah tersebut, diharapkan tercipta ekosistem ekonomi digital yang sehat, adil, dan berkelanjutan di Indonesia.